THE USAGE OF MOTIVATION MEASUREMENT TO INCREASE ORGANIZATIONAL BEHAVIOR ON PT POLYSTAR INTERNATIONAL - Al Fakhry, Achmad Ja'far; Welly, John (Journal of Business and Management, 2015)
Abstract. PT Polystar International is a company engaged in the automotive field in Indonesia, focuses on synthetic leather for covering the car seat, and this is the first company that makes the car seat with synthetic leather that already reaches the National market. The companyâ??s sales always increase every year, and this company is well-known with convincing product quality, hence the position of market leader is irreplaceable by other similar companies to date/now. With the steady growth of this company, this company should also to be supported by a qualified workforce. One of supporting elements that can support the highly qualified workforce is the high motivation of the employees in this company; a qualified workforce will bind organization performance, but until now employeeâ??s motivation in the company is not yet clearly measurable. The aim of my research is to measure the motivation of employees in the company, by using 4-Drives Theory as theoretical basis of this research, because researcher focuses on measure internal motivation, and the extent to which employees are motivated to work in this company. The data taken by distributing questionnaires to all employees in the company which/that the number of respondents are 45 people. The usage of this research is to see clearly the conditions that exist in this company in terms of employee motivation, and determine which the motivation factor that affects to organization performance. Due to the results of this research the company may improve the organizational performance, that accordance to its objectives, the company will always be the market leader.